Simulation of space-based radar observations of precipitations - Khajonrat, Direk, author; Chandra, Chandrasekar V., advisor (Colorado State University. Libraries, 2008)
The Tropical Rainfall Measurement Mission (TRMM) will soon be followed on by the Global Precipitation Measurement (GPM). The GPM satellite will be the next generation observation of precipitation from space. The GPM will carry a dual-frequency precipitation radar (DPR) operating at 13.6 GHz (Ku-band) and 35.6 GHz (Ka-band), as opposed to a single-frequency 13.8 GHz (Ku-band) precipitation radar (PR) in TRMM. A greater degree of accuracy of precipitation measurements can be achieved by a dual-frequency radar using measurements from the two channels. The DPR on the GPM will be the first space-based dual-frequency precipitation radar. Since spaceborne precipitation observations have never been done in Ka-band before, extensive research on dual-frequency radar, including electromagnetic wave propagation characteristics from space and retrieval algorithms are essential for system development and system evaluations. Because the DPR is the first of its kind, a simulation-based study can provide significant assessment of the GPM system which is presented here. The research reported here focuses on developing methodologies for simulating the precipitation characteristics that would be observed from space by DPR using current space-based radar observations and earth-based radar measurements. The underlying microphysics of precipitation structures are important for developing a simulation model and a realistic model of precipitation is desired for representative simulation results. In this research; a microphysical model of precipitation is developed based on airborne radar measurements. The simulation of precipitation observations in Ku- and Ka-band are performed using both TRMM-PR observations and ground-based radar measurements. The simulation of a wide variety of precipitation regimes reveals the characteristics of the precipitation observed in Ku- and Ka-band, and allows testing of different retrieval algorithms-either the single-frequency (TRMM-like algorithm) or dual-frequency techniques. A significant degradation of signal in the Ka-band channel in intense precipitation such as an intense convective storm and tropical storms directly affect the retrieval algorithms that can be used. Vertical reflectivity profiles classification and drop size distribution parameters estimation of tropical storms are studied and results are presented here.
Keywords: precipitation; radar observations; space-based radar; electrical engineering; remote sensing